Acute compartment syndrome of the forearm after trans-radial approach to percutaneous coronary intervention: a case report - Istan Irmansyah Irsan; Satria Pandu Persada Isma; Alifian Alifian; Muhammad Alwy Sugiarto (Universitas Gadjah Mada, 2023)
Percutaneous coronary intervention (PCI) through transradial pathway is associated with lower risk of severe vascular problems comparing to transfemoral. It is reported that the acute compartment syndrome (ACS) in forearm is significant lower comparing to leg. A 47 y.o. male with ACS following a transradial approach of PCI due to inferior myocardial infarction was reported. The patient experienced pain and swelling in his right forearm for 7 hr after the procedure and was later brought to hospital and treated with emergency of fasciotomy. The patient showed good post-fasciotomy recovery on the first 2 wk and showed good DASH score after 4 wk. Quick diagnosis with prompt treatment makes a better outcome for the patient. Consequently, a high level of awareness to make the diagnosis as quickly and accurately management as possible could prevent morbidity caused by late and unrecognized management compartment syndrome eventually could make a better clinical outcome.